Worker Betas: Five Facts about Systematic Earnings Risk - Guvenen, Fatih; Schulhofer-Wohl, Sam; Song, Jae; Yogo, Motohiro (American Economic Review, 2017)
The magnitude of and heterogeneity in systematic earnings risk has important implications for various theories in macro, labor, and financial economics. Using administrative data, we document how the aggregate risk exposure of individual earnings to GDP and stock returns varies across gender, age, the worker's earnings level, and industry. Aggregate risk exposure is U-shaped with respect to the earnings level. In the middle of the earnings distribution, aggregate risk exposure is higher for males, younger workers, and construction and durable manufacturing. At the top of the earnings distribution, aggregate risk exposure is higher for older workers and finance.